Multimedia Pembelajaran Aritmatika Sosial Dengan Pendekatan Realisthic Mathematic Education (RME) Untuk Sekolah Dasar - Sri Tomo (STMIK Sinar Nusantara, 2013)
Mathematics should be given to all students ranging from elementary school to equip students with the ability to think logically, analytical, systematic, critical, and creative, as well as the ability to cooperate. Multimedia Technology is one in the field of computer technology that has the ability to make the media more complete learning. Multimedia summarizes the various media in a container, so as to facilitate the delivery of learning materials and the user can be involved in the learning process.Realistic Approach Mathematic Education (RME) is one of the mathematics learning oriented mathematic everyday experience and apply mathematics in everyday life. Based on the examples presented in accordance with the real world into the visual learning students are expected to enhance students' understanding of the concept of social arithmetic and can increase student motivation. Key Word: Realistic Mathematic Education